Hierarchy within the mammary STAT5-driven Wap super-enhancer - Shin, Ha Youn (Nat Genet, 2016)
Super-enhancers comprise of dense transcription factor platforms highly enriched for active chromatin marks. A paucity of functional data led us to investigate their role in the mammary gland, an organ characterized by exceptional gene regulatory dynamics during pregnancy. ChIP-Seq for the master regulator STAT5, the glucocorticoid receptor, H3K27ac and MED1, identified 440 mammary-specific super-enhancers, half of which were associated with genes activated during pregnancy. We interrogated the Wap super-enhancer, generating mice carrying mutations in STAT5 binding sites within its three constituent enhancers. Individually, only the most distal site displayed significant enhancer activity. However, combinatorial mutations showed that the 1,000-fold gene induction relied on all enhancers. Disabling the binding sites of STAT5, NFIB and ELF5 in the proximal enhancer incapacitated the entire super-enhancer, suggesting an enhancer hierarchy. The identification of mammary-specific super-enhancers and the mechanistic exploration of the Wap locus provide insight into the complexity of cell-specific and hormone-regulated genes.